Characterization of the growth and production of essential oil from “erva baleeira” (Varronia curassavica Jaqc) (Research, Society and Development, 2021)
Research results have confirmed the medicinal attributes of “erva baleeira” (Varronia curassavica Jaqc.) species with metabolic with anti-inflammatory and analgesic properties and which is included in the official list of medicinal plants of value recognized by the Brazilian Ministry of Health. These constituents are present in the leaves and branches that are used in the preparation of teas or used by the industry to extract the essential oil. The objective of this study was to characterize the growth and production of oil of the species in the conditions of Parnaíba, Piauí, Brazil. In the trial, a completely randomized design was adopted, with six treatments, consisting of specimens from matrices grown in six plots of one plantation, four replications and four plants per treatment. Number of inflorescences at thirty days after planting, beginning of fruiting, total height, stem diameter, number of live plants and essential oil production were evaluated. The data were submitted to analysis of variance and means were compared by Tukey test at the significance level of 5%. After one year, few flowers were found at thirty days after planting, ripe fruits at ninety days of planting and an average height of 80.2 cm. Through the three extractions performed, an average production of 0.72 mL of oil was obtained from 500 g of fresh leaves. There were significant differences in the quantities obtained in the different extractions. Growth and production were influenced by nematodes, which caused the death of most plants and decreased the amount of oil extracted.